Synthesis and toxicity assessment of Coffea arabica extract-derived gold nanoparticles loaded with doxorubicin in lung cancer cell cultures - Trejo-Teniente, Isaí; Jaramillo-Loranca, Blanca Estela; Vargas-Hernández, Genaro; Villanueva-Ibáñez, Maricela; Tovar-Jiménez, Xochitl; Olvera-Venegas, Patricia Nayeli; Tapia-Ramírez, José (Frontiers in Bioengineering and Biotechnology, 2024)
Cancer is the second leading cause of death worldwide. Despite the many available treatments, patients with cancer experience side effects that reduce their quality of life. Therefore, development of novel strategies to increase the efficacy of cancer treatments is imperative. In this study, gold nanoparticles obtained by green synthesis with Coffea arabica extract were loaded with doxorubicin (a highly effective but non-specific drug) by direct interaction and using commercial organic ligands that allow colloidal dispersion at physiological and tumour pH. The conjugation of these components resulted in greater specificity and cytotoxicity in H69 tumour cells.